2016
DOI: 10.1111/jocn.13337
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to fear of falling among community‐dwelling older adults

Abstract: Understanding correlates of fear of falling among older Vietnamese people contributes to healthcare professionals' ability to develop effective cross-cultural and culture-specific interventions to reduce older people's fear of falling and to improve quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
82
2
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 36 publications
(50 reference statements)
11
82
2
11
Order By: Relevance
“…() found that older patients without a FOF performed the TUG test better than those who had a FOF. Hoang, Jullamate, Piphatvanitcha, and Rosenberg () reported that a FOF correlated with balance as well as with TUG. In addition, a FOF was associated with physical activity level (Jefferis et al., ; Moreira Bde et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…() found that older patients without a FOF performed the TUG test better than those who had a FOF. Hoang, Jullamate, Piphatvanitcha, and Rosenberg () reported that a FOF correlated with balance as well as with TUG. In addition, a FOF was associated with physical activity level (Jefferis et al., ; Moreira Bde et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have examined the falls in those aged over 60 or 65. Community‐based studies of individuals aged 60 or over have found fall frequencies ranging from 11.3% to 44.5% . According to the WHO Global Report, 28%‐35% of people aged 65 and over fall each year, and this rate increases to 32%‐42% for those over 70 years of age .…”
Section: Discussionmentioning
confidence: 99%
“…The difference in frequency may also be caused by recall bias based on retrospective data collection or the use of different assessment tools. Older people's fear of falling frequency is between 43.3% and 86% . A study conducted in the Netherlands with people aged 80 or over found a rate of fear of falling of 65.6% .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations